Facilitação pode incrementar a capacidade de adaptação de actinobactérias e rizóbios "in vitro" - Silva, Valéria Maria Araújo (2016)
The natural environment is marked by an intricate network of biotic interactions that shape the structure of ecological communities. The presence of positive ecological interactions between microbial populations in soils semiarid regions, has great importance in structuring the local soil microbiota. In this work, actinomycetes strains of rhizobia and coming from rhizosphere of Park National Ubajara-CE, were evaluated for the ability to grow through cooperative metabolic mechanisms. Of the 27 evaluated actinomycetes, 22 showed compatibility with rhizobia. The strains UB-05, UB-07, UB-08, UB-11 and UB-21 stood out in facilitating tests for amylase and cellulase. The metabolic activity of actinomycetes helped the development of rhizobia strains.